PERANCANGAN SISTEM INFORMASI SCM PADA UD. MEBEL JAYA - Tri Siska Wati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Technology and information today are growing rapidly and have a major influence on human behavior and habits. Computers are very helpful and facilitate human work, effective and efficient computer work produces accurate information so that many companies use information technology to improve their quality in all aspects, namely to compete in the business world, therefore UD. Mebel Jaya needs to implement a Supply Chain Management Information System (Supply Chain Management) which aims to facilitate inventory management, starting from the process of ordering goods from suppliers, procurement of goods to managing goods to customers. UD.Mebel Jaya is a business engaged in the furniture manufacturing industry which focuses on the production of furniture / furniture such as tables, chairs, cabinets, and frames. The system is made using a web-based system design and uses supporting applications such as XAMPP and the Hypertext Preprocessor (PHP) programming language and DBMS (Database Management System) using MySQL, it is hoped that this application can help companies store all data that is still using a manual system, or not computerized system with the aim of maximizing performance and profit for the company, suppliers, including customers and can provide satisfaction to suppliers and companies so that carrying out business processes will be easy.